Effective Cooperation of Academic and University Science. An interview with Yevstahii KRYZHANIVSKI, the Principal of the Ivano-Frankivsk National Technical University of Oil and Gas, Full Member of the NAS of Ukraine - Zaliznyak, B.V. (Science and Innovation, 2024)
.